Mothers and Fathers—Who Matters for STEM Performance? Gender-Specific Associations Between STEM Performance, Parental Pressure, and Support During Adolescence - Hoferichter, Frances; Raufelder, Diana (Frontiers in Education, 2019)
Research has shown that parental pressure is negatively whereas parental support is positively associated with various scholastic outcomes, such as school engagement, motivation, and achievement. However, only few studies investigate boys' and girls' perception of mother and father pressure/support in detail. This might be particularly essential when it comes to girls' and boys' achievement in STEM subjects, as girls and boys might profit differently from parental pressure/support regarding their achievement in STEM and vice versa. This study aims to shed light on this topic and explores potential within—and over time associations between students' perception of parental pressure/support and grades in mathematics and biology. Using self-report data from 1,088 8th grade students at T1 (Mage = 13.70, SD = 0.53, 54% girls) from Brandenburg, Germany, multigroup cross-lagged models were conceptualized with Mplus. The results indicate that there are gender differences in the interplay of students' grades in mathematics, biology, and their perception of parental pressure and support: Whereas, mother support plays a central beneficial role for girls' achievement in STEM subjects as well as for the other parental variables over time, for boys mother support is negatively associated with math performance over time. Within-time associations further show that boys—in contrast to girls—do not benefit from any parental support regarding their performance in mathematics or biology. Finally, results suggest that the relationship between adolescents' STEM achievement and parental pressure/support is rather mono-directional than bi-directional over time.